تطوير مهارة الكلام باستخدام الطريقة الانتقائية وتقنية سرد القصص المصورة: Developing Speaking Skills Using the Selective Method and Comic Storytelling Technique - Wahyuni, Sri; Mawardi, Mawardi (Institut Agama Islam Negeri (IAIN) Palopo, 2024)
This research examines the implementation of a selective method combined with comic storytelling techniques to enhance Arabic speaking skills among eleventh-grade students. The objectives are to: (1) analyze how the selective method with comic storytelling improves students’ speaking skills and (2) evaluate the outcomes of its application. Conducted as Classroom Action Research (CAR), the study involved two cycles, each consisting of planning, action, observation, and reflection. The results demonstrate a notable improvement in students' speaking abilities. The average score increased from 69.58 before the intervention to 75.15 in the first cycle and 92.92 in the second cycle, classified as